OP0083 PREVALENCE OF VERTEBRAL FRACTURES IN POSMENOPAUSAL WOMEN WITH RHEUMATOID ARTHRITIS. (June 2019) - Vaquero, Carmen Gómez; Cerda, Dacia; Hidalgo, Cristina; López, Ja Martínez; Rodríguez, Luis Marcelino Arboleya; Rey, Javier Aguilar del; Pardo, Silvia Martinez; Ros, Inmaculada; Surís, Xavier; Grados, Dolors; Beltrán, Chesús; Suero-Rosario, Evelyn; et al.
Abstract : Background: Rheumatoid arthritis (RA) is a risk factor for the development of fragility fractures, but there is little quality data on its prevalence. Conversely, osteoporosis is one of the most frequent comorbidities of RA. Objectives: To determine the prevalence of vertebral fractures in postmenopausal women with RA and to analyse their characteristics and associated risk factors. Methods: We included 346 postmenopausal women diagnosed with RA according to the ACR/EULAR 2010 criteria in 19 Spanish Rheumatology Departments, randomly selected from the registry of RA patients in each center, recruited during 2018. Lateral radiographs of the dorsal and lumbar spine were obtained from all patients, to evaluate morphometric vertebral fractures. Expert rheumatologists identified vertebral fractures and classified them into mild (grade 1: reduction of height of 20-25%), moderate (grade 2: reduction of 26-40%) and severe (grade 3: reduction > 40%), according to the Genant grading scale. The spinal deformity index (SDI) was calculated by assigning numbers 1, 2 and 3 to each fractured vertebra and adding the total score of each patient. The study variables were: a) age, body mass index (BMI), b) factors related to RA: time of evolution, FR, ACPA, and c) fracture risk factors: prior fragility fracture, parental hip fracture, glucocorticoids, smoking, alcohol intake ≥3 units daily, secondary osteoporosis and time since menopause. Results: The mean age was 66.8 (SD: 10.1) years and the median evolution of the disease, 8.00 [RIQ: 3.00-15.5] years. 77.2% (n: 267) and 75.7% (n: 252) had FR and ACPA +, respectively. The mean duration of the postmenopausal period was 15.0 (SD: 9.6) years. 23.4% (n: 79) of patients had at least one vertebral fracture; 10.7% (n: 36) had a single fracture and 12.7% (n: 43), multiple fractures. The most fractured vertebrae were D12, L1 and L2 (fractured in > 5% of patients). The median SDI was 3 [RIQ: 2-5]. The vertebrae with the highest mean IDE were D8, D10, D11 and L1 (all mean IDE ≥ 2).An association was found between the presence of vertebral fractures and age, height, postmenopausal period, time of disease progression, glucocorticoid treatment and parental hip. No linear association was found between SDI and age, time of evolution of the disease, BMI and time since menopause. Conclusion: One out of every 4 postmenopausal women with RA has at least one vertebral fracture. Vertebrae of the dorso-lumbar hinge are the most frequently involved and the magnitude of the spinal deformity is relevant. Vertebral fractures are related to the time of evolution of RA and to the risk factors for fracture. Disclosure of Interests: Carmen Gómez Vaquero: None declared, Dacia Cerda: None declared, Cristina Hidalgo: None declared, JA Martínez López: None declared, Luis Marcelino Arboleya Rodríguez: None declared, Javier Aguilar del Rey: None declared, Silvia Martinez Pardo: None declared, Inmaculada Ros: None declared, Xavier Surís Speakers bureau: Lilly, Pfizer, MSD, Dolors Grados: None declared, Chesús Beltrán: None declared, Evelyn Suero-Rosario: None declared, Inmaculada Gómez Gracia: None declared, Asunción Salmoral: None declared, Irene Martín-Esteve: None declared, Helena Florez: None declared, Antonio Naranjo: None declared, Santos Castañeda Consultant for: Amgen, BMS, Pfizer, Lilly, MSD, Roche, Sanofi, UCB, Soledad Ojeda Grant/research support from: AMGEN, Speakers bureau: AMGEN, S García Carazo: None declared, Alberto García-Vadillo: None declared, Laura López Vives: None declared, À Martínez-Ferrer: None declared, Helena Borrell: None declared, Pilar Aguado: None declared, Raul Castellanos-Moreira Speakers bureau: MSD, Lilly, Núria Guañabens Consultant for: Advisory Boards from Amgen, Alexion and UCB, Speakers bureau: Fees and lectures from Eli Lilly